2022
DOI: 10.4314/ahs.v22i1.65
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis mixed infections and drug resistance in sub-Saharan Africa: a systematic review

Abstract: Background: Sub-Saharan Africa, is a region that records high rates of TB infection. Mycobacterium tuberculosis mixed strain infection, especially when the strains involved are of different susceptibilities, is an area of great interest because it is linked with an increased risk of treatment failure and transmission of resistant strains within the population. This paper reviewed original studies that reported MTB mixed infection and heteroresistance in the region between 2010 and 2020 to understand the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…The Sub-Saharan African region has a high tuberculosis incidence. An article examined studies in Sub-Saharan Africa from 2010 to 2020 that reported mixed tuberculosis infection and heteroresistance [ 80 ]. Several databases were examined, but only 18 papers matched the inclusion criteria.…”
Section: Antimicrobial Resistance Data In African Countriesmentioning
confidence: 99%
“…The Sub-Saharan African region has a high tuberculosis incidence. An article examined studies in Sub-Saharan Africa from 2010 to 2020 that reported mixed tuberculosis infection and heteroresistance [ 80 ]. Several databases were examined, but only 18 papers matched the inclusion criteria.…”
Section: Antimicrobial Resistance Data In African Countriesmentioning
confidence: 99%
“…If generalizable across populations, these findings suggest that reinfection does occur in humans but is the minority of cases, complicating the interpretation of epidemiological data in the context of understanding concomitant immunity. Other studies from areas with high levels of endemic TB 6,7 reported the detection of multiple Mtb strains in the sputum of both HIV negative and positive individuals providing stronger and direct evidence that reinfection occurs in humans. The small numbers make it difficult to conclude with certainty whether HIV increases the rate of reinfection, but they do report a higher proportion of HIV positive patients carrying multiple Mtb strains, potentially implicating CD4+ T cells or other immune factors as important players in restricting reinfection with Mtb.…”
Section: Introductionmentioning
confidence: 95%